Guidelines Concerning the Academic Mandatum in Catholic Universities (Canon 812) - , United States Conference of Catholic Bis (Catholic Education: A Journal of Inquiry and Practice, 2001)
Recommended procedures for granting, withholding, or withdrawing the mandatum required for Catholics who teach theological disciplines in the U.S. Catholic colleges and universities were approved June 15 by a voice vote of the U.S. bishops during the spring meeting in Atlanta. The mandatum was called for in a bishops’ document (Origins, Vol. 30, pp. 65ff) applying Pope John Paul II’s 1990 apostolic constitution on Catholic higher education, Ex Corde Ecclesiae (Vol. 20, pp. 265ff), in the United States. The June 15 text says that its “guidelines are intended to explain and serve as a resource for the conferral of the ”˜mandatum.’ Only those guidelines herein that repeat a norm of the [application document] have the force of particular law.” The nature of the mandatum, how it is to be granted, what is to be done if a professor does not request it, and considerations related to its denial are among concerns the document addresses (an earlier draft text of the procedures appeared in Origins, Vol. 30, pp. 425ff). “The ”˜mandatum’ recognizes both the professor’s ”˜lawful freedom of inquiry’ and the professor’s commitment and responsibility to teach authentic Catholic doctrine and to refrain from putting forth as Catholic teaching anything contrary to the Church’s magisterium,” the document says. It observes, “Theologians who have received a ”˜mandatum’ are not catechists; they teach in their own name in virtue of their baptism and their academic and professional competence, not in the name of the bishop or of the church’s magisterium.” The new document notes that “the ”˜mandatum’ is an obligation of the professor, not of the university”; it explains that the Catholic theological disciplines in this context are “sacred Scripture, dogmatic theology, moral theology, pastoral theology, canon law, liturgy, and church history.” The text says that “ecclesiastical authority should presume, until the contrary is proven, that those who attest that they teach in full communion with the Church actually do so.” It says, “Any negative judgment concerning an objectionable portion of a professor’s work should be assessed at three levels: (1) the significance of that portion of the professor’s work within the context of his or her overall theological contribution; (2) its relationship to the larger Catholic tradition; (3) its implications for the life of the Church.” The text of the recommended procedures includes sample letters for requesting and granting the mandatum. The text, copyright 2001, by the U.S. Catholic Conference, follows. (See also the “On File” page of June 28, 2001, Origins for a report on discussion of the mandatum during the bishops’ meeting.)